How science saved the Eiffel tower - Smith, Emma Bland (Capstone Editions, 2022)
A nonfiction picture book that describes how the people of Paris were critical of the tower that Gustave Eiffel was building. Although they came to love it after it was completed, it was slated to be torn down in 1909, unless Monsieur Eiffel could give it purpose. Details how Eiffel found ways to use the tower for experiments with weather, air resistance, and wireless communications, thereby saving it forever. Includes a list of French terms, facts about the Eiffel Tower, and a timeline of events.